The ecology of sandy shores - McLachlan, Anton 1949- (London Academic Press, 2018)
The Ecology of Sandy Shores, Third Edition, provides both a holistic and conceptual introduction for beginners, while also presenting an in-depth and cutting-edge analysis for researchers interested in sandy shores. This new edition focuses on resource use, and has also been updated to include recent findings, enhanced illustrations, and additional coverage on beach fisheries and global/climate change. In addition, this release presents insights on food webs, greater coverage on global biodiversity patterns in sandy beaches, and new insights on population patterns, behavior and threats. Research on beaches is difficult because of the dynamic nature of the environment. There is no other book covering the ecology of sandy beaches, despite the extent and economic importance of these systems. This book is designed to both provide the conceptual basis to introduce students to the basic principles of sandy shore ecology and to serve as a ready reference for doctoral students and researches working on these systems. It can also serve as a handbook for land and coastal managers.--Provided by publisher.
Electronic reproduction.
Keywords: Seashore ecology; Sand dune ecology; Beaches; Electronic books